Crosstalk between Innate Lymphoid Cells and Other Immune Cells in the Tumor Microenvironment. (12th October 2016) - Flores-Borja, Fabian; Irshad, Sheeba; Gordon, Peter; Wong, Felix; Sheriff, Ibrahim; Tutt, Andrew; Ng, Tony
Abstract : Our knowledge and understanding of the tumor microenvironment (TME) have been recently expanded with the recognition of the important role of innate lymphoid cells (ILC). Three different groups of ILC have been described based on their ability to produce cytokines that mediate the interactions between innate and adaptive immune cells in a variety of immune responses in infection, allergy, and autoimmunity. However, recent evidence from experimental models and clinical studies has demonstrated that ILC contribute to the mechanisms that generate suppressive or tolerant environments that allow tumor regression or progression. Defining the complex network of interactions and crosstalk of ILC with other immune cells and understanding the specific contributions of each type of ILC leading to tumor development will allow the manipulation of their function and will be important to develop new interventions and therapeutic strategies.